Question about Office Equipment & Supplies

# Y=2x-3 x+y=18 what is the answer to this question

Posted by on

• Level 3:

An expert who has achieved level 3 by getting 1000 points

Superstar:

An expert that got 20 achievements.

All-Star:

An expert that got 10 achievements.

MVP:

An expert that got 5 achievements.

• Master

X = 7
Y = 11

Posted on Nov 14, 2014

Hi there,
Save hours of searching online or wasting money on unnecessary repairs by talking to a 6YA Expert who can help you resolve this issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

Here's a link to this great service

Good luck!

Posted on Jan 02, 2017

×

my-video-file.mp4

×

## Related Questions:

### 2x plus 5y equals 7 3x plus 6y equals 3

1) 2x + 5y = 7
2) 3x + 6y = 3

I'm going to use the method of elimination to solve for x and y.
Multiply 1) by 3 and 2) by 2 to allow the x's to be eliminated.

1) 6x + 15y = 21
2) 6x + 12y = 6

Now subtract line 2 from line 1.

0x + 3y = 15
---- ----
3 3 divide both sides by 3 to get y by itself.
y =5.
Substitute into 1) to calculate x.
2x + 5(5) = 7
2x + 25 = 7
2x + 25 -25 = 7 - 25
2x = -18
---- ----- divide both sides by 2 to get x by itself
2 2

x = -9

Check by plugging in answer into the other equation, in this case 2)

3 (-9) + 6(5) = 3
-27 + 30 = 3
3 = 3
We did it correctly and checked to prove that we did it right.

Good luck.

Paul

Mar 12, 2015 | Office Equipment & Supplies

### I need to understand how to divide a binomial.

Let's take 2x^2 - 10x +12 and divide it by x-2.
__2x_-_6____________
x-2 ) 2x^2 - 10x + 12
2x^2 - 4x
------------
- 6x + 12
- 6x + 12
------------
0

How many times does x go into 2x^2. Put the answer, 2x above the 2x^2. Next mulitply (x-2) by 2x and put the answer under 2x^2. Now subtract that answer from 2x^2 - 10x and we get -6x (-10x - (-4x)).

How many time does x go into -6x. -6 time. Write this above the line and put the answer above the -10x. Next multiply (x-2) by -6 and put the answer under the -6x. Subtract and we get 0 and we are done. If we want to check our answer we can multiply (x-2) and (2x - 6) and we should get 2x^2 - 10 x + 12.

Good luck.

Paul

Oct 03, 2014 | Office Equipment & Supplies

### What is the answer for y=2x=6

this is a simle equation.
to solve it, you need to move the known to one side of the = (equal) sign and the onknown to the other side. every step shown, does not change the values of x or y.
y=2x=6
2x=6=y
2x=6=y
x=6:2=y
X=3=y

Dec 16, 2013 | Computers & Internet

### 4x - 2x + 1 = 5 + x - 7

1. Combine like terms on the left side of =

4x-2x =2x

New left side is 2x + 1

2. Combine like terms on right side of =

5 - 7 = -2

New right side is x - 2

3. New problem is 2x + 1 = x - 2

4. Now get all x terms on left side of =
and all constants on right side of = by adding the opposites of the corresponding terms as you move them across the =

2x - x = -2 - 1

5. Combine the like terms on each side of the =

Left side: 2x - x = x and Right side: -2 -1 = -3

So x = -3

4(-3) - 2(-3) + 1 = 5 + (-3) -7

7. Now do the arithmatic and hopefully the left and right sides are equal.

-12 + 6 +1 = 5 -3 -7
-5 = -5

Since this is a true statement I know my answer of x = -3 is the correct solution to this problem.

May 17, 2012 | SoftMath Algebrator - Algebra Homework...

### How to identify the x and y intercepts for a line

Hi Melissa:

2x + (2x-3) - 6 = 0
4x - 9 = 0
x = 9/4

Then y = 3/2

Thank you for using Fixya, and have a nice day.

Nov 16, 2011 | Computers & Internet

### 2x+y=1 x=-2,0,1 y=

This has nothing to do with laptops, please remove it from this section. The answer is 2x+y=1 so y=1-2x therefore 1-(2X-2) =1--4 Y= 5 so do the same thing again 1-(2X0) 1-0 Y=1 and again 1-(2X1) 1-2 Y=-1

Jan 25, 2011 | Computers & Internet

### Find the value of the variable ''x'' 6x+6=4x+12

6x+6=4x+12
Since 4x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 4x from both sides.
6x+6-4x=12
Since 6x and -4x are like terms, add -4x to 6x to get 2x.
2x+6=12
Since 6 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 6 from both sides.
2x=-6+12
Add 12 to -6 to get 6.
2x=6
Divide each term in the equation by 2.
(2x)/(2)=(6)/(2)
Simplify the left-hand side of the equation by canceling the common factors.
x=(6)/(2)
Simplify the right-hand side of the equation by simplifying each term.
x=3

Good Luck

Sep 10, 2009 | Audio Players & Recorders

### How do i use the cal for cube problems

You are asking how to enter (3)(cube of 2x)-1, or (3)(cube of (2x-1), with x = -13?

For first:

13
=/- (below 3 key)
X
2
=
2nd
x cubed (above 1 key)
X
3
-
1
=

For second:

13
=/- (below 3 key)
X
2
-
1
=
2nd
x cubed (above 1 key)
X
3
=

Aug 01, 2008 | Texas Instruments TI-30XA Calculator

### Memory and memory recal

The STO> button just above the on/off button is your memory store initializer.
example: 2x + 53 STO> y
stores "2x + 53" in a variable named "y".
To recall, just hit y and enter. In fact, if you type an equation like 3y^2 - 4y it will insert the data in for every "y" and give you:
(2x + 53)(6x + 155) as an answer.
To clear the memory:
DelVar y or F6 (2nd+F1) and clear all w/ single character names.
To recall a prevous answer, 2nd+(-) or type ans(1) for the last answer. You can also type ans(2) for the 2nd to last answer & so on.

Jan 30, 2008 | Texas Instruments TI-30 XIIS Calculator

## Open Questions:

#### Related Topics:

29 people viewed this question

Level 3 Expert

Level 3 Expert